A qualitative research on the relationship between entrepreneurial behaviour and innovative work behavior - Gunes, Evrim; Sekerdil, Resat (Pressacademia, 2022)
Purpose – The purpose of this study is to reveal the entrepreneurial and innovative behavior tendencies and skills of Y and Z generations based on experiences and perceptions, and to provide an understanding of the problems these generations face while collaborating and the needs necessary for their cooperation. Methodology– In order to obtain in-depth information about the subject, the qualitative research method was used in the research. Semi-structured interviews were conducted with the entrepreneur mentors of Ege University Technopolis and the entrepreneurs in the technopolis. The sample consists of 8 people in total. The data were analyzed with descriptive and content analysis. Findings – The expressions of the participants were evaluated under the themes of entrepreneurship and innovation skills of the Z generation and the entrepreneurship and innovation perceptions of the Y generation, which emerged as a result of the analysis. Entrepreneurship and innovation skills for the Z generation; being a researcher, being aware of what one wants, agility, social relations, being able to offer different suggestions, self-confidence, being open-minded, being open to learning, being result-oriented, being proactive, taking risks, having business management knowledge. For the perception of entrepreneurship and innovation of the Y generation; commercial perception, innovation barriers, time, scaling, realism, and result-oriented qualities came to the fore. Conclusion – Entrepreneurship is often defined in terms of risk taking, self-confidence and proactive behavior. These general behavior patterns are not well understood in entrepreneurship and innovation surveys. There are many more factors to be discovered for scaling these concepts. In this study, it was revealed that in order to be an entrepreneur, it is necessary to be innovative first, and being innovative is related to openness to learning and frequency of experimentation in addition to general behavior patterns. Keywords: Innovative work behavior, entrepreneural behavior, entrepreneurship, innovation. JEL Codes: M10, O30, L26 Purpose – The purpose of this study is to reveal the entrepreneurial and innovative behavior tendencies and skills of Y and Z generations based on experiences and perceptions, and to provide an understanding of the problems these generations face while collaborating and the needs necessary for their cooperation. Methodology– In order to obtain in-depth information about the subject, the qualitative research method was used in the research. Semi-structured interviews were conducted with the entrepreneur mentors of Ege University Technopolis and the entrepreneurs in the technopolis. The sample consists of 8 people in total. The data were analyzed with descriptive and content analysis. Findings – The expressions of the participants were evaluated under the themes of entrepreneurship and innovation skills of the Z generation and the entrepreneurship and innovation perceptions of the Y generation, which emerged as a result of the analysis. Entrepreneurship and innovation skills for the Z generation; being a researcher, being aware of what one wants, agility, social relations, being able to offer different suggestions, self-confidence, being open-minded, being open to learning, being result-oriented, being proactive, taking risks, having business management knowledge. For the perception of entrepreneurship and innovation of the Y generation; commercial perception, innovation barriers, time, scaling, realism, and result-oriented qualities came to the fore. Conclusion – Entrepreneurship is often defined in terms of risk taking, self-confidence and proactive behavior. These general behavior patterns are not well understood in entrepreneurship and innovation surveys. There are many more factors to be discovered for scaling these concepts. In this study, it was revealed that in order to be an entrepreneur, it is necessary to be innovative first, and being innovative is related to openness to learning and frequency of experimentation in addition to general behavior patterns. Keywords: Innovative work behavior, entrepreneural behavior, entrepreneurship, innovation. JEL Codes: M10, O30, L26